Construction Labour Relations Association in Canada - Rose, Joseph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper examines the relatively recent movement by employers in the construction industry toward province-wide associations specializing in labour relations. Beginning with the formation of the Construction Labour Relations Association of British Columbia (CLRA) it reviews the influences of contractor cooperation, union opposition and labour laws on the ability of these organizations to bring unity to contractor ranks and alleviate what has been de-scribed as the imbalance of power in construction labour relations. There is also an examination of the organizational characteristics of these CLRA-type organizations which reveals how they have been able to maintain control of members and reduce fragmentation